Search for the rare decay B-s(0) -> mu(+)mu(-) - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (Elsevier B.V., 2010)
We present the results of a search for the flavor changing neutral current decay B-s(0) -> mu(+)mu(-) using 6.1 fb(-1) of p (p) over bar collisions at root s = 1.96 TeV collected by the D0 experiment at the Fermilab Tevatron Collider. The observed number of B-s(0) candidates is consistent with background expectations. The resulting upper limit on the branching fraction is B(B-s(0) -> mu(+)mu(-)) < 5.1 x 10(-8) at the 95% C.L. This limit is a factor of 2.4 better than that of the previous do analysis and the best limit to date. Published by Elsevier B.V.
Keywords: b-quarks; Rare decays